PENGARUH KETERLIBATAN ORANG TUA TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS VI SEKOLAH DASAR - Sulistiyanto, Edy (INOPENDAS: Jurnal Ilmiah Kependidikan, 2023)
The purpose of the study was to describe the effect of parental involvement on mathematics learning outcomes conducted at SD Negeri 3 Jambu, Mlonggo District, Jepara Regency. Types of Methods This research uses a descriptive qualitative approach with data collection techniques of data triangulation, namely data collection techniques that combine various data collection techniques and data sources that already exist. Qualitative research is a research approach that represents naturalistic (phenomenological) understanding. Questionnaires were obtained from the parents of grade VI students with a total of 34 respondents. The result of this study is to find out the extent of parental involvement in mathematics learning outcomes. Parental involvement in Mathematics Learning for Grade VI students of SD Negeri 3 Jambu in the 2021/2022 academic year obtained from filling out a questionnaire/questionnaire of twenty questions with the criteria of Never with one point, Rarely with two points, Frequent criteria with three points and criteria Always with four points. The results obtained are the criteria of Never having a percentage of zero, the criteria of Rarely having a result of six percent, the criteria of Often reaching forty-seven percent, and the criteria of Always reaching forty-four percent. While the results of the assessment obtained by students with the criteria of Less reached fifty percent, Enough criteria were twenty-nine percent, Good criteria reached twenty-one percent and Very Good criteria were zero percent.